Does protein intake correlate with tubular function in very preterm neonates? - Henny Adriani Puspitasari; Partini Pudjiastuti Trihono; Pustika Amalia Wahidiyat (Paediatrica Indonesiana, 2023)
Background High protein intake in very preterm neonates (VPN) is important for growth. However, preterm kidneys have fewer functional nephrons and many of the ones present may be immature. Studies have shown that high protein intake induces nephron hypertrophy, proteinuria, and glomerular sclerosis, which lead to tubular injury. Urinary neutrophil gelatinase-associated lipocalin (uNGAL) is a biomarker that is released during proximal tubular cell injury. The uNGAL to creatinine (uNGAL/Cr) ratio is commonly performed for normalization. Objective To assess for a possible association between protein intake and uNGAL/Cr ratio in VPN. Methods A prospective cohort study was conducted in two NICUs in Jakarta. Subjects’ urine specimens were collected at 0-48 hours, 72 hours, and 21 days after birth to determine uNGAL/Cr ratio as a biomarker of tubular injury. Protein was administered according to study sites NICU guidelines. Protein intake was recorded daily from 14-21 days of age for formula and measured twice with a human milk analyzer for breast milk. ELISA was used to measure uNGAL concentration. Low protein intake was defined as <3g/kg/day and high protein intake was defined as ?3g/kg/day. Maternal and perinatal variables were recorded from medical records. Results Fifty-nine VPN were recruited, of whom 39 completed the study. Median uNGAL/Cr ratio ranged from 0.32-104.11 ng/mg. The uNGAL/Cr ratio was not correlated with protein intake but was inversely correlated with gestational age and birth weight [r = -0.320, P=0.019 for the 72-hr (T2) urinary collection]. Higher uNGAL/Cr levels were associated with maternal infection [14.4 (range 4.4-104.1) vs 7.2 (range 0.5–32.4) ng/mg, P=0.004 at the 0-48-hr (T1)], maternal anemia [6.9 (range 1.2–66.6) vs 1.7 (range 0.3–89.2) ng/mg, P=0.001 at the 21-day (T3)] and nephrotoxic medication [15.9 (range 1.3–63.8) vs 1.0 (range 0.4–8.6) ng/mg, P=0.026 at the 72-hr]. Conclusion Protein intake according to current nutritional guidelines does not correlate with tubular injury in VPN, as measured by uNGAL/Cr ratio. Maternal infection, maternal anemia, lower birth weight, and nephrotoxic medication, were associated with higher uNGAL/Cr levels in VPN.